2015
DOI: 10.1097/prs.0000000000000987
|View full text |Cite
|
Sign up to set email alerts
|

SERI Surgical Scaffold, Prospective Clinical Trial of a Silk-Derived Biological Scaffold in Two-Stage Breast Reconstruction

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 17 publications
3
32
0
Order By: Relevance
“…As the number of mastectomies and subsequent reconstructions continue to increase, and with the evolving nature of the reimbursement in healthcare, cost may become a significant limiting factor. Other options include utilizing ADM as an anterior sling, in which only the entire anterior aspect of the prosthesis is covered by ADM. 34 In addition, synthetic mesh products, including vicryl, 7,34 silk, 50 and titanium 24,41,51 derivatives, among others, may be a less expensive alternative, and have shown promising results. Mesh was less commonly utilized in the studies in this review, likely because of its more recent introduction in implant-based breast reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…As the number of mastectomies and subsequent reconstructions continue to increase, and with the evolving nature of the reimbursement in healthcare, cost may become a significant limiting factor. Other options include utilizing ADM as an anterior sling, in which only the entire anterior aspect of the prosthesis is covered by ADM. 34 In addition, synthetic mesh products, including vicryl, 7,34 silk, 50 and titanium 24,41,51 derivatives, among others, may be a less expensive alternative, and have shown promising results. Mesh was less commonly utilized in the studies in this review, likely because of its more recent introduction in implant-based breast reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-six of 139 subjects were excluded from the PP population, 28 of whom received unplanned radiation therapy after implantation. 8 The other 8 subjects were excluded for various reasons, including not receiving a breast implant, having another support device implanted, being involved in another clinical trial, and not meeting eligibility criteria. All satisfaction, effectiveness, and safety analyses were performed on the PP population, which included 103 subjects (161 breasts).…”
Section: Resultsmentioning
confidence: 99%
“…Study design and eligibility criteria were previously reported. 8 Briefly, this prospective, multicenter, single-arm study enrolled women who received SERI during stage 1 of 2-stage breast reconstruction. Subjects included women undergoing breast reconstruction with subpectoral placement of a tissue expander (Natrelle Style 133V; Allergan plc, Dublin, Ireland) followed by exchange with a breast implant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a protocol described in recent publications (24,25) we are making pockets with pectoralis major on the inner upper region of the breast, sutured to a mesh silk (SERI™ Surgical Scafffold, Allergan, California, USA) in the outer lower region achieving full coverage of the expander and evaluate whether this technique provides the same results in terms of complications and aesthetics, which completely muscular pocket ( Figure 10). The patient's smoking status must also be assessed with regard to the reduction of necrosis.…”
Section: Complicationsmentioning
confidence: 99%